Establishment of Nepal’s first provincial infectious and communicable disease hospital in Gandaki Province - Gauchan, Bikash (Journal of General Practice and Emergency Medicine of Nepal, 2021)
In December 2019, Sudden deaths of people due to pneumonia caused by the new Coronavirus (SARS-Cov-2) in Wuhan, China and its rapid spread to other countries forced World Health Organization to declare pandemic on 12 March 2021. With first case on 13 January 2020, Nepal started preparing to manage COVID – 19. The government of Nepal made historic decision to establish an infectious and communicable disease hospital in each province. The Gandaki province government decided to establish provincial infectious and communicable disease hospital on 12th April 2020. The newly established hospital has now become Nepal’s first provincial infectious and communicable disease hospital. Future research will establish the effectiveness of provincial dedicated infectious and communicable disease hospital.